Comparative phytochemical and in vitro antimicrobial activities of the leaf extracts of two medicinal plants growing in North-East, Nigeria - Hamidu Usman; Muhammad Awwal Tijjani; Abudlkarim Hassan; Zainab Babagana Aji (Shahrekord University of Medical Sciences, 2018)
Introduction: The use of plants as medicine is as old as chemistry and common to all societies including the African, notably some parts of Northern Nigeria. Infectious diseases are among the causes of mortality and morbidity in rural areas endemic with hygienic problems in most developing countries including Nigeria. Two plant species with similar ethnomedical reports from different families were used in this study against some microorganisms. Their phytochemicals were also evaluated. Methods: The leaf samples of Punica granatum and Waltheria indica were prepared and independently extracted with 80% methanol using maceration technique. The extracts were concentrated to dryness at reduced pressure and then subjected to phytochemical evaluation. Antimicrobial activities were evaluated using hole-in-plate disc diffusion technique. Results: The phytochemical results of both extracts revealed the absence of anthraquinones. However, both extracts showed the presence of cardenolides, cardiac glycosides, flavonoids, saponins, tannins and terpenoids; while alkaloids were found in W. indica. The antimicrobial susceptibility study showed dose-dependent pattern with the highest dose (80 mg/hole) showing inhibition zone of 23.67 ± 0.47 and 23.33 ± 0.47 mm, respectively by P. granatum and W. indica against Streptococcus pyogenes while at 20 mg/hole inhibition was noted as 8.67 ± 0.47 and 7.00 ± 0.00 mm against Escherichia coli for P. granatum and W. indica, respectively. Conclusion: The findings of this study scientifically support the use of P. granatum and W. indica in folklore medicine for the cure of infections by microbes.